“Mayores conectados”: Designing and developing public library services to bridge the digital divide of older adults - de-la-Calle-Hernández, María-del-Carmen; García-Jáñez, Eva-Margarita; Gómez-Díaz-Ortiz, María-Sierra; Gonzalo-Ortiz, Elena; Mena-Macías, Natividad; Ramos-Claudio, Rafael; Rebollo-Arranz, Alberto-Francisco (Revista de Investigación sobre Bibliotecas, Educación y Sociedad, 2024)
Public libraries can contribute positively to overcoming the digital divide and the feeling of social exclusion of older adults through the design and development of services based on information and digital literacy. This article describes the workshop "Mayores Conectados" carried out by the Municipal Public Library Ángel González of Madrid. The project is based on the acquisition of skills for the use of smartphones as a mobile technology. There are several studies reporting a lack of services in libraries for the elderly in Spain; and that is the basis of this article and the workshop presented. The article includes a review of the literature on public libraries, the elderly and the digital divide; and the main points of the workshop, including its objectives, its execution and the positive impact on the participants and the award achieved. The originality of the article lies in the fact that it provides knowledge for the design and development of services in libraries focused on the digital divide of older adults, promoting social values such as inclusion, family relations and friendship.
Keywords: Public libraries; Older adults; Library services; Digital divide; Information literacy; Social exclusion; Social inclusion; Digital skills; Mobile technologies; Mobile phones; Smartphones